Long term dietary Moringa oleifera leaf extract to Florida red tilapia Oreochromis sp improves performance immunity maturation and reproduction in saltwater - Ghada R. Sallam; Mohamed M. Abdel-Rahim; Ayman M. Lotfy; Walied M. Fayed; Akram Ismael Shehata; Mohammed F. El Basuini; Rasha I. Elwan; Mohamed A. Al-absawey; Ashraf I. G. Elhetawy (Scientific Reports)
Abstract High salinity impairs offspring production in Florida red tilapia (FRT) Oreochromis sp. A total of 624 FRT broodstock (1:1 ratio of ♂: ♀) were divided into 16 groups, with 4 males and 4 females housed separately at two salinity levels (18 ppt and 32 ppt). Fish were fed four different levels of Moringa oleifera leaf extract (MOLE) supplementation (0, 5, 10, and 15 g MOLE kg−1 diet) for two months. Following the initial feeding period, males and females receiving the same MOLE level under the same salinity conditions were transferred to 24 spawning concrete tanks. The experiment consisted of eight groups, each containing 3♂ and 6♀, with triplicate setups (four groups at 18 ppt and four groups at 32 ppt). Fish were fed at 1% of their body weight for four months. The results revealed significant (p < 0.05) improvements in water quality (lower ammonium and nitrite), growth parameters, feed conversion ratio, carcass protein content, digestive enzymes, liver enzymes, cortisol level, innate immunity, antioxidants, testosterone and progesterone hormones, and reproductive function (♂ and ♀) with MOLE-fed broodstock in both salinities. MOLE at 10–15 g/kg can improve FRT performance, welfare, fertility (♀), and reproduction under high salinity conditions (32 ppt).